« Voir le mouvement » par une « image du mouvement » : éducation et représentation du mouvement, entre science, art et euphorie chez Georges Demenÿ à partir de 1900 - Marie Gueden (Mise au Point)
Based on the writings of Georges Demenÿ around 1900 on the education of movement, between art and science, we examine how the body in transformation of the young girl and boy in a pioneer of cinema who was also a gymnast and pedagogue is the subject of a construction and is expressed as much by discourse and practices as by graphic representations to be apprehended in relation to Mareysian graphic modelling: these images of movement are less theoretical than practical and axiological, with a high educational value, serving to perfect the vision of movement and education in ease, with a view to a general feeling of well-being, euphoria.